Positive correlations between the health locus of control and self-management behaviors in hemodialysis patients in Xiamen - Jia-Li Fan; Yue Kong; Su-Hua Shi; Yu-Hong Cheng (Elsevier, 2016)
Objective: To investigate the association between the health locus of control and self-management behaviors in patients receiving hemodialysis. Methods: Patients receiving hemodialysis in Xiamen, Fujian province, from December 2014 to March 2015 answered the Chinese version of the Multidimensional Health Locus of Control scale and the self-management behavior questionnaire. Results: The participants in this study indicated that they believed others exerted more control over their health than themselves or chance. In addition, the majority of participants had a medium to low level of self-management behaviors. Positive correlations were also observed between a participant's health locus of control and their level of self-management behaviors. Internal health locus of control and external (others) health locus of control were significant predictors of self-management behaviors controlling for the effect of payment method. Conclusion: The results of this study provided evidence that there is a strong relationship between the health locus of control and self-management behaviors in hemodialysis patients. This study provides important information for medical professionals as they design strategies to educate hemodialysis patients on their health locus of control and self-management behaviors. Keywords: Hemodialysis, Health locus of control (HLC), Self-management behaviors